PEMBUATAN SABUN TRANSPARAN DENGAN PENAMBAHAN KITOSAN SISIK IKAN DAN JERUK KALAMANSI - Wica Elvina; Devi Silsia; Yessy Rosalina; Wuri Marsigit; Ulfah Anis (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This study aimed to determine the effect of adding fish scale-derived chitosan and Calamansi (Citrus microcarpa), a local commodity widely available in Bengkulu Province, on the quality of transparent soap. The parameters analyzed included moisture content, pH, foam stability, and antimicrobial activity. The results showed that the physical characteristics of transparent soap differed mainly in color. Soap containing chitosan from tilapia scales exhibited a clear yellow color, while soap made with snapper scale chitosan showed a darker, orange-yellow hue. Chemically, both formulations met the Indonesian National Standard (SNI 3532:2016), with pH values ranging from 9.84 to 10.45, indicating safe use for the skin. The moisture content ranged from 10.5% to 11.2%, below the maximum SNI limit of 15%, suggesting good stability and a potentially longer shelf life. Foam stability exceeded 90%, demonstrating that fish scale chitosan contributed to the formation of stable foam. Antimicrobial testing revealed that soap containing tilapia scale chitosan exhibited stronger inhibition zones against Staphylococcus aureus (14.1 mm) and Escherichia coli (12.6 mm) compared to soap containing snapper scale chitosan.